Handbook of research on reinventing economies and organizations following a global health crisis - Costa, Teresa Gomes da, 1964-; Lisboa, Ines Margarida, 1981-; Teixeira, Nuno Miguel, 1974- (Business Science Reference, 2021)
"This book provides insights about changes in business, institutions, and economies during and post COVID-19, as well as to provide information to entrepreneurs and managers for dealing with entrepreneurship and innovation, networks and complementarities in order to recover businesses"--